Screening of anthelmintic and insecticidal activity of Flacourtia jangomas fruit pulp - Islam, Shah Md. Nasrul (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.